Giant cell lesion of the jaw as a presenting feature of Noonan syndrome. (30th May 2018) - Sinnott, Bridget P; Patel, Maya
Abstract : This is a case of a 20-year-old woman who presented with a left jaw mass which was resected and found to be a giant cell granuloma of the mandible. Her history and physical examination were suggestive for Noonan syndrome which was confirmed with genetic testing and the finding of a PTPN11 gene mutation which has rarely been associated with giant cell lesions of the jaw. Given her particular genetic mutation and the presence of a giant cell lesion, we present a case of Noonan-like/multiple giant cell lesion syndrome.